CIRCULATING OXIDIZED LOW-DENSITY LIPOPROTEIN LEVELS IN AN EARLY STAGE OF ACUTE ISCHEMIC STROKE - Tosheska Trajkovska, Katerina; Emin, Melda; Ampova Hristina; Kerala, Coskun; Kostovska, Irena; Topuzovska, Sonja (Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, 2024)
Introduction: Atherosclerosis remains the most common cause of coronary artery disease (CAD) and cerebral or peripheral artery disease. At present, lipid peroxidation is considered one of the basic mechanisms involved in the initiation and progression of many diseases. An oxidative stress resulting in lipid peroxidation and protein modification is involved in the pathogenesis of atherosclerosis and cardiovascular diseases. Aim: The primary aim of this study was to determine the circulating levels of oxidized low-density lipoprotein (ox-LDL) in patients with acute stages of ischemic stroke. The secondary aim was to evaluate if there was an association between ox-LDL concentration and conventional lipid risk factors for cardiovascular diseases (CVD). Material and methods: Seventy-five patients with acute ischemic stroke (AIS) and ninety control subjects without cardiovascular risk factors were included in the study. Total cholesterol, triglycerides, HDL-cholesterol, and LDL-cholesterol were measured in patients as well as in control subjects by enzymatic methods on Roche C311 Cobas Analyzer. Ox-LDL was measured by the sandwich ELISA technique. Results: There was no significant difference in BMI, total cholesterol, triglycerides, HDLc, and LDL-c between the two groups. There was a significant difference between patients with AIS and the control group regarding ox-LDL concentrations (p=0.03). We did not find any significant correlation between plasma ox-LDL concentration and lipid parameters. Conclusions: Levels of circulating ox-LDL were elevated in patients with acute ischemic stroke. Ox-LDL levels were not statistically correlated with major lipid risk factors for CVD. Therefore, ox-LDL levels may represent a novel risk marker of CVD.
Keywords: ox-LDL; stroke; cardiovascular disease